Cue combination in human spatial navigation - Chen, Xiaoli; McNamara, Timothy P.; Kelly, Jonathan W.; Wolbers, Thomas (Cognitive psychology, 2017)
•Spatial cues were weighted in terms of their relative reliabilities in spatial navigation.•Landmark instability reduced reliance on landmarks by impairing cue reliability.•Distorted feedback influenced cue reliability.•Subjective evaluation of self-performance contributed to cue weighting. This project investigated the ways in which visual cues and bodily cues from self-motion are combined in spatial navigation. Participants completed a homing task in an immersive virtual environment. In Experiments 1A and 1B, the reliability of visual cues and self-motion cues was manipulated independently and within-participants. Results showed that participants weighted visual cues and self-motion cues based on their relative reliability and integrated these two cue types optimally or near-optimally according to Bayesian principles under most conditions. In Experiment 2, the stability of visual cues was manipulated across trials. Results indicated that cue instability affected cue weights indirectly by influencing cue reliability. Experiment 3 was designed to mislead participants about cue reliability by providing distorted feedback on the accuracy of their performance. Participants received feedback that their performance with visual cues was better and that their performance with self-motion cues was worse than it actually was or received the inverse feedback. Positive feedback on the accuracy of performance with a given cue improved the relative precision of performance with that cue. Bayesian principles still held for the most part. Experiment 4 examined the relations among the variability of performance, rated confidence in performance, cue weights, and spatial abilities. Participants took part in the homing task over two days and rated confidence in their performance after every trial. Cue relative confidence and cue relative reliability had unique contributions to observed cue weights. The variability of performance was less stable than rated confidence over time. Participants with higher mental rotation scores performed relatively better with self-motion cues than visual cues. Across all four experiments, consistent correlations were found between observed weights assigned to cues and relative reliability of cues, demonstrating that the cue-weighting process followed Bayesian principles. Results also pointed to the important role of subjective evaluation of performance in the cue-weighting process and led to a new conceptualization of cue reliability in human spatial navigation.